Energy analysis of wet season rice production in Northern Thailand - Tanate Chaichana (2018)
This study was designed to record the production factors, analyze energy consumption and formulated the mathematical model for prediction energy requirement in the future of wet season rice production. The study areas were located in six provinces of Northern Thailand. The rice production process comprised of soil preparation, cultivation, cultural practice and harvest. During these processes, production factors were determined and changed to an equivalent value of energy consumption per production area (MJ/Rai). Subsequently, they were calculated for a multiple correlation of production factors and energy consumption in order to estimating future energy requirement. It was found that in order to obtain an average paddy yield of 626.26 kg/Rai, the average commercial energy consumption was 2,246.65 MJ/Rai and non-commercial energy consumption was 181.11 MJ/Rai. So, the average energy consumption was 2,427.76 MJ/Rai. The majority part of energy is from chemical fertilizer of 39.25% of total energy following by the energy from agriculture machinery of 35.46% and 17.23%, 3.39%, 4.07% and 0.06% for the energy from fuel, labor, seed and chemical substance respectively. Farmers should reduce the chemical fertilizer and use more organic fertilizer which is not only lower the energy consumption and cost but also save the environment and keep healthy. The mathematical model is accurately to predicting the energy consumption and planning to use the production factors in the future. The model is not depending on production factors price, but it is up to the quantity of using. © 2008 AAAE.